Pengembangan Hilirisasi Tembaga dan Perannya Dalam Mendorong Industri Produk Akhir Nasion - Alieftiyani Paramita Gobel; M. Ridha Addavari; M. Dhaffa Faatihah; Oreza Marzendy Sumarsyah (Sinergi : Jurnal Ilmiah Multidisiplin, 2026)
The development of copper downstreaming has become a priority strategy due to the increasing global demand for copper in line with the energy transition, while domestic added value remains limited due to the dominance of concentrate exports. This study aims to map the copper downstreaming value chain at the national level, its contribution to the development of final industrial products, and identify challenges and opportunities for policy and technical implementation. The method used is a systematic desk study with a qualitative descriptive approach, combining secondary data from scientific literature, industry reports, and policy documents to synthesize quantitative evidence and qualitative arguments related to upstream–midstream–downstream capacity, inter-industry needs, and circular economy practices. The study results indicate that increasing midstream capacity (smelters/refineries) has the potential to increase cathode supply and open up space for the production of semi-finished products and value-added final products but realizing these benefits requires supply integration (feedstock), off-take/TKDN policies, long-term financing, and technical human resource development. Copper recycling has also emerged as an important pillar for resilience and reducing the environmental footprint. In conclusion, copper downstreaming can effectively promote the national final product industry if implemented through a coherent policy that combines midstream investment, downstream industry incentives, financing schemes, and a circular economy strategy. Keywords: copper downstreaming, value chain, end products, industrial policy, recycling   Abstrak Pengembangan hilirisasi tembaga menjadi prioritas strategis karena permintaan tembaga global yang meningkat sejalan dengan transisi energi, sementara nilai tambah domestik masih terbatas akibat dominasi ekspor konsentrat. Penelitian ini bertujuan memetakan rantai nilai hilirisasi tembaga di tingkat nasional, mengevaluasi kontribusinya terhadap pengembangan industri produk akhir, serta mengidentifikasi tantangan dan peluang implementasi kebijakan dan teknis. Metode yang digunakan adalah studi pustaka sistematis dengan pendekatan deskriptif kualitatif, memadukan data sekunder dari literatur ilmiah, laporan industri, dan dokumen kebijakan untuk mensintesis bukti kuantitatif dan argumen kualitatif terkait kapasitas hulu–midstream–hilir, kebutuhan industri antar, serta praktik circular economy. Hasil kajian menunjukkan bahwa peningkatan kapasitas midstream (smelter/refinery) berpotensi meningkatkan pasokan katoda dan membuka ruang bagi produksi produk setengah jadi serta produk akhir bernilai tambah namun realisasi manfaat tersebut mensyaratkan integrasi pasokan (feedstock), kebijakan off-take/TKDN, pembiayaan jangka panjang, serta pengembangan SDM teknis. Daur ulang tembaga juga muncul sebagai pilar penting untuk ketahanan pasokan dan pengurangan jejak lingkungan. Kesimpulannya, hilirisasi tembaga efektif mendorong industri produk akhir nasional jika dilaksanakan melalui kebijakan koheren yang menggabungkan investasi midstream, insentif industri hilir, skema pembiayaan, dan strategi circular economy.   Kata kunci: hilirisasi tembaga, rantai nilai, produk akhir, kebijakan industri, daur ulang